Pulmonary diffusing capacity in healthy Caucasian children - Kim, Y.; Hall, Graham; Christoph, K.; Tabbey, R.; Yu, Z.; Tepper, R.; Eigen, H. (Wiley-Liss, Inc, 2012)
Previous studies of pulmonary diffusing capacity in children differed greatly in methodologies; numbers of subjects evaluated, and were performed prior to the latest ATS/ERS guidelines. The purpose of our study was to establish reference ranges for the diffusing capacity to carbon monoxide (DLCO) and alveolar volume (VA) in healthy Caucasian children using current international guidelines and contemporary equipment. Healthy children from the United States (N = 303) and from Australia (N = 176) performed acceptable measurements of single breath pulmonary diffusing capacity and alveolar volume according to current ATS/ERS guidelines. The natural log of DLCO and VA were associated with height, age and an age–sex interaction term, while DLCO/VA was related to height and the age–sex interaction term only. Adjustment of DLCO for hemoglobin (n = 303; USA data only) resulted is a small but significant decrease in DLCO of ∼1% but did not significantly alter the regression equations. In this dataset there was no influence of center for DLCO or DLCO/VA, while Australian children had a statistically smaller VA (mean difference 0.14 L after accounting for height, age and age–sex; P = 0.012). We report that diffusing capacity outcomes can be collated from multiple centers using similar equipment and collection protocols. Using collated data we have derived regression equations for pulmonary diffusing capacity outcomes in healthy Caucasian children aged 5–19 years. Pediatr Pulmonol.